PARADIGMA PENDIDIKAN DALAM PERSPEKTIF SURAH AL-ALAQ AYAT 1-5 - Said, Colle (State Institute of Islamic Studies (IAIN) Palu, 2016)
Education is a matter of life and life (life is education and education is life). The whole process of life and human life is a process of education. Thatâs the reason why the first paragraph in Qurâan is paragraph on education dropped the first five verses of surah al-âAlaq. The paradigm of education in the perspective of surah al-âAlaq verse 1-5, aims to develop basic human potential, so that he can become a caliph in the earth. Education can play a humanitarian role as a caliph on earth, is education that refers to a conceptual foundation, namely education based on two fundamental teachings of the Muslim beliefs and morals are as hinted in surah al-âAlaq verses 1-5. Through education pattern-based beliefs or morals, human being smart, have the provision of living a life in dignity, peaceful, responsible, confident and not easily manipulated.